EKSISTENSI SD IT DALAM PEMBELAJARAN ALQURAN DI KOTA MEDAN - Suryadi Nasution (Tadrib: Jurnal Pendidikan Agama Islam, 2021)
This study explains the importance of inclusive education in the reality of Islamic education. In addition, this study also highlights the dynamics that occur in the implementation of inclusive education so This study aims to describe the implementation of the Qur'anic learning program at SD IT Medan City. The concept built in this research approach is a comparative study with mixed research analysis. The Qur'an learning program at SD IT Medan City is generally carried out at the beginning of the lesson along with the implementation of other religious programs. The ability of SD IT Kota students in reading the Koran has matured (tartil) at the 4th grade level. In addition, being able to memorize juz 30 ('Amma) is a mandatory requirement for students to complete their studies.In data management (analysis), this research uses mixed method research. Where the data collected are in two forms, namely, quantitative form, and qualitative form. Data in the form of quantitative means data in the form of numbers that are presentative in nature, such as percentage figures for comparison of student achievement in reading the Koran, efficiency figures for memorizing the Koran targets, and so on. The data in the form of numbers are not analyzed by statistical formulas, but are analyzed in qualitative form with a narrative analysis patternBased on the results of the study, the Koran learning activities displayed by SD IT focused on the practice of learning religion in the classroom. In this learning, in addition to providing curricular religious lessons, religious teachers are also required to provide iqra' Al-Qur'an learning.